2009
DOI: 10.1111/j.1601-183x.2009.00506.x
|View full text |Cite
|
Sign up to set email alerts
|

Oxytocin and the oxytocin receptor underlie intrastrain, but not interstrain, social recognition

Abstract: We studied three lines of oxytocin (Oxt) and oxytocin receptor (Oxtr) knockout (KO) male mice (Oxt−/−, total Oxtr−/−, and partial-forebrain Oxtr (OxtrFB/FB)) with established deficits in social recognition to further refine our understanding of their deficits with regard to stimulus female's strain. We used a modified social discrimination paradigm in which subjects are singly housed only for the duration of the test. Additionally, stimulus females are singly-housed throughout testing and are presented within … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
77
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(83 citation statements)
references
References 31 publications
(53 reference statements)
6
77
0
Order By: Relevance
“…First, male rodents engineered to lack (fore-brain) oxytocin receptors no longer discriminate between familiar and unfamiliar females, whereas normal rodents spent more time investigating unfamiliar female rodents versus female rodents with whom they had shared a cage for several days (Macbeth et al, 2009; also see Ferguson et al, 2000Ferguson et al, , 2002. Along similar lines, participants who memorized pictures of faces under oxytocin performed better one day later on measures of familiarity, indicating that oxytocin makes a face in memory more familiar (Rimmele et al, 2009).…”
Section: Social Bond Formation and Maintenancementioning
confidence: 99%
“…First, male rodents engineered to lack (fore-brain) oxytocin receptors no longer discriminate between familiar and unfamiliar females, whereas normal rodents spent more time investigating unfamiliar female rodents versus female rodents with whom they had shared a cage for several days (Macbeth et al, 2009; also see Ferguson et al, 2000Ferguson et al, , 2002. Along similar lines, participants who memorized pictures of faces under oxytocin performed better one day later on measures of familiarity, indicating that oxytocin makes a face in memory more familiar (Rimmele et al, 2009).…”
Section: Social Bond Formation and Maintenancementioning
confidence: 99%
“…In order to preserve their own colony and strain, mice are more likely to mate within their strain (Macbeth et al 2009). In order to determine the ability of our transgenic mice to form a memory of a mouse of another strain, we tested the animals in a short-term (1 h) and long-term (24 h) social recognition task using white BALB/c juvenile male mice as the stimulus.…”
Section: Social Recognition Across Mouse Strainsmentioning
confidence: 99%
“…In addition to long-term social recognition, rodents are also known to form transient short-term memories of recently encountered individuals (Thor and Holloway, 1982). Since a pioneering study on oxytocinknockout mice by Ferguson and colleagues (Ferguson et al, 2000), it has been revealed that oxytocin receptor (OTR) knockout mice fail to develop short-term memory (Macbeth et al, 2009;Takayanagi et al, 2005) as assessed by a habituation-dishabituation paradigm. In a series of these studies, it was shown that OTR-knockout mice could not distinguish between familiar and novel encounters with mice from the same strain, suggesting that the oxytocin system is involved in "fine" intrastrain recognition in mice (Macbeth et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Since a pioneering study on oxytocinknockout mice by Ferguson and colleagues (Ferguson et al, 2000), it has been revealed that oxytocin receptor (OTR) knockout mice fail to develop short-term memory (Macbeth et al, 2009;Takayanagi et al, 2005) as assessed by a habituation-dishabituation paradigm. In a series of these studies, it was shown that OTR-knockout mice could not distinguish between familiar and novel encounters with mice from the same strain, suggesting that the oxytocin system is involved in "fine" intrastrain recognition in mice (Macbeth et al, 2009). However, it was shown that OTR-knockout male mice could distinguish between familiar and novel females from different strains in the habituation-dishabituation paradigm, suggesting that the oxytocin system is less important in "broad" interstrain recognition in mice (Macbeth et al, 2009).…”
Section: Introductionmentioning
confidence: 99%